Health economic burden of COVID-19 in Saudi Arabia - Alenzi, Khalidah A.; Al-malky, Hamdan S.; Altebainawi, Ali F.; Abushomi, Hamidah Q.; Alatawi, Fahad O.; Atwadi, Moosa H.; Khobrani, Moosa A.; Almazrou, Dlal A.; Alrubeh, Nariman; Alsoliabi, Zainab A.; Kardam, Abdulaziz M.; Alghamdi, Shakr A.; et al. (Frontiers in Public Health, 2022)
Abstract Background: The coronavirus disease 2019 (COVID-19) pandemic has added a massive economic burden on health care systems worldwide. Saudi Arabia is one of the numerous countries that have been economically affected by this pandemic. The objective of this study was to provide real-world data on the health economic burden of COVID-19 on the Saudi health sector and assess the direct medical costs associated with the management of COVID-19. Methods: A retrospective cohort study was conducted based on data collected from patients hospitalized with COVID-19 across ten institutions in eight different regions in Saudi Arabia. The study calculated the direct medical costs of all cases during the study period by using SAS statistical analysis software. These costs included costs directly related to medical services, such as the health care treatment, hospital stays, laboratory investigations, treatment, outcome, and other related care. Results: A total of 5,286 adult patients admitted with COVID-19 during the study period were included in the study. The average age of the patients was 54 years, and the majority were male (79%). Among the COVID-19 patients hospitalized in a general ward, the median hospital length of stay was 5.5 days (mean: 9.18 days), while the ICU stay was 4.2 days (mean: 7.94 days). The total medical costs for general ward and ICU patients were US 3,889,5 and US 24,207,296.9, respectively. The total laboratory investigations ranked as the highest-cost services US 5,889,75 followed by treatment US 3,886,509.8. Overall, the total cost of all medical services for patients hospitalized with COVID-19 was US 51,572,393.45. Conclusion: This national study found that COVID-19 was not only a serious concern for patients but also a serious economic burden on the health care system in Saudi Arabia.